Design and Development of the "Campoga" Sports Field Reservation System Based on a Website - Siregar, Nicolas; Githa, Dwi Putra; Sasmita, Gusti Made Arya (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2025)
The development of this web-based sports field reservation information system aims to accelerate the reservation process and management of field reservation data. This system is expected to manage reservation data more efficiently and accurately. The purpose of this study is to understand how to design and build a web-based sports field reservation information system, known as Campoga. The method used in the development of this system is the Waterfall method. The result of this study is the creation of a web-based sports field reservation information system, built using Laravel, MySQL database, and Visual Studio Code as the testing editor.